Low-carbon optimal operation of the integrated energy system considering integrated demand response - Ji, Xiu; Li, Meng; Li, Meiyue; Han, Huanhuan (Frontiers in Energy Research, 2023)
In order to further reduce the carbon emission level of the integrated energy system and improve the system operation economy, a low-carbon economic dispatch strategy for the integrated energy system considering comprehensive demand response is proposed. First, based on the composition and operating characteristics of the integrated energy system, two demand response models, price-based and substitution-based, are established. Secondly, based on the ladder-type carbon trading mechanism and the green certificate trading mechanism, a green certificate-carbon trading mechanism model is designed to construct a ladder-type carbon trading mechanism model. A comprehensive energy system low-carbon economic dispatch model with the lowest system operating cost is composed of carbon transaction costs, energy purchase costs, operation and maintenance costs, green certificate trading income and wind and light abandonment costs. Finally, through simulation experiments, this paper is verified the effectiveness of the proposed model is analyzed, and the impact of demand response sensitivity and ladder-type carbon trading mechanism parameters on system dispatch results is analyzed.